The Power Consumption Performance of an Orbiting Screw Solid-Solid Mixer - Semuel Pati Senda; Renanto Renanto; Achmad Roesyadi; Wahono Sumaryono; Yazid Bindar (Journal of Engineering and Technological Sciences, 2012)
In this work we have investigated mixing in a modified orbiting screw mixer  (MOSM)  designed  for  solid-solid mixing.  Mixing  was  carried  out  using urea powder and natural zeolite powder (UZ) of three varying particle sizes (50-60, 60-80 and 80 mesh). Power consumption was calculated from the measured torque of orbit and screw, obtained from computerized records. It was found that the  mixing  process  in  the  modified  orbiting  screw  mixer  with  air  injection required a lower power consumption for each particle-size group when compared to mixing without air injection. With UZ mixing in MOSM with  air injection, the lowest E was obtained for  the 60-80 mesh particle-size group  (4,297 Joule/kg-1),whereas when mixing without  air injection, the value was  10,296 J/kg. The best mixing  operation in this experiment was achieved at NFr  =  1.18x10-3 and in the range  of  values  NReâ‰ˆ  8.77x107 to  2.63x108.  Moreover,  in this  study,  we  have developed  an  equation  to  estimate the  power  consumption required  for  mixing and determined its correlation with dimensionless numbers.